Scheduling Optimization Model for Highway Port Network Tractor and Semitrailer Dispatching Considering Time Window under Unbalanced Demand - Shaoquan Ni, Hongxia Guo (Forest Chemicals Review, 2021)
Tractor and semitrailer transportation, as a common organization form of cargo transport, is an effective way to improve road transport efficiency and reduce transport costs. At present, highway port has become an important place for China to carry out tractor and semitrailer transportation. Highway port is not only a site for tractor and semitrailer transportation operations, but also a customer demand point and a trailer pool, so each node in the highway port drop and pull network can be the starting or ending point of tractor and semitrailer transport (depot). Based on the pure network tractor and semitrailer dispatching mode of highway ports, considering that there is unbalanced demand at both operation ends in the tractor and semitrailer transport and there may be multiple tractor and semitrailer demands, this paper aims to achieve the lowest network transport cost and minimum number of tractors. Giving consideration to time window constraints, it establishes a pure network tractor and semitrailer scheduling optimization model, designs an ant colony algorithm and introduces a local search strategy to solve the model. Effectiveness of the model is verified by an example. The research results show that compared with the traditional model, the number of pure network tractor and semitrailer tractors is reduced by 83.5%, the cost is saved by 19.1%, and the tractor and semitrailer ratio is 1:6.06. That is, the use of pure network scheduling optimization will result in better operational performance, thereby reducing costs and increasing profits. The research results provide a certain reference for the pure network tractor and semitrailer vehicle scheduling optimization with balanced demand and multiple demands